Assessment of Residual Virulence of Francisella tularensis 15 NIIEG Vaccine Strain Based on Long-term Observations - L. V. Sayapina; I. I. Khoreva; N. P. Baidalova; A. A. Goryaev; D. S. Davydov; V. P. Postupailo; V. A. Merkulov (Проблемы особо опасных инфекций, 2018)
Objective of the study is to assess and analyze the long-term data on annual control of residual virulence of Francisella tularensis 15 NIIEG vaccine strain for clarifying the value of the parameter and amending the regulatory documentation. Materials and methods. Utilized were 8 vials containing lyophilized cultures of vaccine strain F. tularensis 15 NIIEG dated 1953, 1966, 1969, 1987, 1990, 2003, 2012, and 2013, manufactured at different industrial sites. To gather additional information on residual virulence of F. tularensis 15 NIIEG strain, evaluation of quality control files of 76 lyophilized cultures in vials was performed, out of which 48 strains manufactured at the premises of Odessa Bacterial Products Enterprise in 1980, 1987, and 1990, and 28 – at Joint Stock Company Scientific Production Association on Medical Immunobiological Preparations “Microgen”, Omsk Bacterial Products Enterprise, in 2003–2013. Results and discussion. Assessment of the parameter has revealed that out of 8 tested cultures of F. tularensis 15 NIIEG strain of various date of lyophilization 7 cultures have virulence rate ranging within 1·102 – 2.5·102 mc, LD50 of the strain dated 1966 is 7.3·105 mc (the standard range 1·102 – 2·106 mc). Obtained in the course of analysis of quality control files on F. tularensis 15 NIIEG strain, stored in lyophilized form at (19±1) °C, data demonstrate that residual virulence stays within the specified limits. Amendments regarding the value of “Residual virulence” parameter have been introduced into the regulatory documentation, the level ranging within 1·102 – 5·103 mc.